Correlation between anti-S IgG and neutralizing antibody titers against three live SARS-CoV-2 variants in BNT162b2 vaccine recipients - Yuki Higashimoto; Kei Kozawa; Hiroki Miura; Yoshiki Kawamura; Masaru Ihira; Hiroyuki Hiramatsu; Ryota Suzuki; Kei Haga; Reiko Takai-Todaka; Akihito Sawada; Kazuhiko Katayama; Tetsushi Yoshikawa (Taylor & Francis Group, 2022)
We analyzed serially collected serum samples from healthy adults who underwent BNT162b2 vaccination to elucidate the association between spike (S)-IgG antibody titers determined by ELISA using the WHO international standard (NIBSC code 20/136) and neutralizing antibody titers against three live SARS-CoV-2 variants. This study included 53 health care workers who received two doses of the BNT162b2 vaccine. S-IgG and nucleocapsid (N)-IgG antibody titers were measured by ELISA. Neutralizing (NT) antibody responses against three variants (Wuhan D614 G: KUH003, Alpha, and Delta) were evaluated before and after the first and second vaccination. N-IgG were not detected in any serum samples. S-IgG antibody titers remarkably increased after two BNT162b2 vaccine doses in all participants. S-IgG antibody titers were strongly correlated with NT titers against three variants of live viruses: KUH003 (r = 0.86), Alpha (r = 0.72), and Delta (r = 0.84). Serum samples from participants after one dose of BNT162b2 neutralized Alpha efficiently (median titer, 113.0), but median NT titers against KUH003 and Delta variants were lower, 57.0 and 28.0, respectively (p < .01). Two doses of the BNT162b2 vaccine elicited a strong immune response in this study. The second dose was required for induction of a strong booster effect. Serum collected from BNT162b2 vaccine recipients contained significantly lower neutralizing activity against Delta than that of against KUH003 (p < .0001) and Alpha (p < .0001). If a new variant emerges, live virus-based NT titers should be examined in serum obtained from vaccine recipients to evaluate vaccine efficacy for protection against infection.